Problems of Teachers and Students in Learning the Quran - Pasaleron, Roni; Afrianto, Afrianto; Junaidi, Apri; Rahman, Ikhwan; Susanti, Weti (Al-kayyis: Journal of Islamic Education, 2023)
This research aims to analyze the problems of teachers and students in teaching the Quran. This research uses qualitative methods with a case study approach (case study design), data sources were taken from forty-two informants through in-depth interviews who were selected using techniques purposive sampling. All interview results were then analyzed thematically using Miles and Huberman qualitative data analysis. The findings show that there are twelve problematic findings for teachers and students in learning the Alquran. Teacher problems include the lack of Al-Quran tahsin activities and training for Al-Quran teachers, lack of competence of Al-Quran teachers, teachers having difficulty managing time, large capacity of students in the class, differences in students' backgrounds, difficulty in managing and conditioning students in the classroom, and the lack of welfare of Al-Quran teachers. Problems with students include the low level of focus or concentration of students in learning, lack of discipline among students, lack of enthusiasm for students in learning. Problems with facilities and infrastructure include lack of facilities and infrastructure such as the Alquran, lack of tables for the Alquran. The results of this research can be used as a basis and reference for future researchers to study problems related to this or issues that are different but have similar context and intent.